Multilocus Sequence Typing of Klebsiella Pneumoniae Producing Extended Spectrum Β-Lactamases Isolated From Kurdistan Region, Iraq. - Khalid, Haval M.; Jubrael, Jaladet M.S.; Yousif, Samira Y. (Science Journal of University of Zakho, 2014)
This study was purposed to sequence analysis of ESBLs genotype of K pneumoniae using partial sequence and Multilocus sequence typing (MLST). A total of 275 K. pneumoniae isolatesinvolved three general hospitals in Duhok, Erbil, and Sulymania, from September 2010 to June 2011. The Minimum Inhibitory Concentration (MIC) was measured by Phoenix system that confirmed 187 ESBL producing isolates followed by the Double Disk Synergy Test (DDST). Then, 12 isolates were selectedaccording to sample diversity, high resistancy to β-lactam and cephalosporins and harboring combination of three genes (TEM, SHV, and CTX-M). Partial sequence analysis of TEM; showed two different genotypes regarding blaTEM as 9 isolates (75%) from different samples (wound, sputum and blood) from three provinces harbor TEM-1 gene and 3 isolates (25%) only from urine in three provinces harbor TEM-198 gene. SHV analysis revealed characterization of selected isolates into six different genotypes. The common genotype was blaSHV-11 involved five isolates from sputum and blood in Erbil and Sulymania provinces, and wound in Duhok province. Only one genotype as all 12 isolates (100%) from different samples and different provinces was found harbored CTX-M-15 gene. Multilocus sequence typing (MLST) study performed using seven housekeeping genes (gapA, infB, mdh, pgi, phoE, rpoB and tonB). A total of 8 different sequence types (STs) were identified;ST11 was dominant sequence type, accounting 41.6 %( 5 isolates) and was harboring combination of TEM-1, SHV-11 and CTX-15 genes.